The efficacy and safety of topical wound oxygen therapy for chronic refractory wounds at high altitude: Protocol for a randomized controlled clinical trial. - Shuang Lin; Lihong Chen; Dawei Chen; Yun Gao; Chun Wang; Xingwu Ran (PLoS ONE)
Background The hypobaric and hypoxic characteristic of plateau regions can lead to sustained hypoxia, inadequate tissue perfusion, and an inflammatory response at wounds sites. Topical wound oxygen therapy (TOT) shows potential in elevating transcutaneous oxygen tension, stimulating the production of vascular endothelial growth factor, promoting angiogenesis and tissue remodeling, thereby accelerating wound healing. However, there is a scarcity of research investigating the therapeutic efficacy of TOT for treating chronic refractory wounds in long-term inhabitants of plateau areas. The present study aims to evaluate the efficacy and safety of TOT as a viable treatment option for chronic refractory wounds in individuals residing in high-altitude environments. Positive findings could establish TOT as a valuable and safe complementary strategy for managing such wounds in high-altitude settings. Methods and analysis This study is a randomized controlled clinical trial involving 250 patients residing at high altitudes. Participants will be randomly assigned to receive either TOT or sham oxygen therapy over a 12-week period, followed by a one-year follow-up. In addition to the experimental interventions, all participants will receive standard care for their chronic wounds. The primary outcome measure is the wound healing rate at the end of the 12-week intervention. Secondary endpoints include the reduction in ulcer area after intervention, the time required for ulcer healing, the recurrence rate of ulcers, the amputation rate, pain levels, and any adverse events. Trial registration The trial has been officially registered in the Chinese Clinical Trial Registry, and assigned the registration number ChiCTR-2400083602.